Women leadership at the head of the Pan-African Farmers' Organisation: the Integrated Rural Development Strategy - Ben Rejeb, Fatma (Technical Centre for Agricultural and Rural Cooperation, 2019)
Fatma Ben Rejeb is the Chief Executive Officer of the Pan-African Farmers' Organisation (PAFO). PAFO is a network of Farmers' Organisations across the African continent that aims to improve communication, collaboration and information/knowledge sharing among stakeholders. It is Africa's first continent-wide farmers' organisation and is an important instrument for rallying direct farmer engagement on Africa's growth and development agenda. Fatma spoke to ICT Update about PAFO's work with women and digitalisation.